Betulinic acid induces apoptosis of gallbladder cancer cells via repressing SCD1. (8th January 2020) - Wang, Hongfei; Dong, Fangxiao; Wang, Ye; Wang, Xu'an; Hong, Defei; Liu, Yingbin; Zhou, Jian
Abstract: Gallbladder cancer (GBC) is the most common and aggressive malignancy of the biliary tract. Betulinic acid (BetA) has been reported to have anti-inflammatory and antitumor effects; however, the effect of BetA on GBC is still unknown. In this study, we investigated the effect of BetA on five GBC cell lines and found that BetA significantly inhibited the proliferation of NOZ cells but had little inhibitory effect on other GBC cells. BetA disturbed mitochondrial membrane potential and induced apoptosis in NOZ cells. Real-time polymerase chain reaction analysis revealed that stearoyl-coenzyme A desaturase 1 ( SCD1 ) was highly expressed in NOZ cells but low expressed in other GBC cells. BetA inhibited SCD1 expression in a concentration-dependent manner in NOZ cells. Downregulation of SCD1 expression by RNA interference inhibited the proliferation of NOZ cells and induced cell apoptosis. Moreover, BetA inhibited the growth of xenografted tumors and suppressed SCD1 expression in nude mice. Thus, our results showed that BetA induced apoptosis through repressing SCD1 expression in GBC, suggesting that BetA might be an effective agent for the treatment of patients with GBC that highly expresses SCD1 .